2015
DOI: 10.1016/j.jtumed.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Sotos syndrome with developmental co-ordination disorder; report of a case

Abstract: Sotos syndrome (Cerebral Gigantism) a rare genetic disorder is usually characterized by macrocephaly and typical facial gestalt. There is a spectrum of behavioral and cognitive problems associated with it. We present a case of 11-year-old boy who presented with coordination issues, academic difficulties along with host of behavioral problems. On examination he was tall and had macrocephaly with typical facial gestalt. His educational assessment revealed the presence of developmental co-ordination disorder (DCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Aggressive behaviour and/or tantrums were reported in six studies [ 25 , 31 , 38 , 43 – 45 ] and were assessed through parental report or psychiatric assessment (see Table 3 ). Of these studies, five employed a case study design and only one of the case studies used a female participant [ 45 ], despite the syndrome affecting males and females equally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggressive behaviour and/or tantrums were reported in six studies [ 25 , 31 , 38 , 43 – 45 ] and were assessed through parental report or psychiatric assessment (see Table 3 ). Of these studies, five employed a case study design and only one of the case studies used a female participant [ 45 ], despite the syndrome affecting males and females equally.…”
Section: Resultsmentioning
confidence: 99%
“…However, deBoer et al [ 24 ] found no significant difference between mean scores of the Sotos group and the control group, on the 18-item Dutch ADHD list. Within the case studies that measured behavioural features of individuals with Sotos syndrome, a total of five participants were reported to have a clinical diagnosis of ADHD [ 33 , 38 , 43 , 47 ]. In addition, two cases were reported of individuals who were inattentive, hyperactive and demonstrated a lack of inhibition [ 33 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with typically developing children, those with Sotos syndrome show higher rates of behavioral problems (Lane et al, 2016). Although a spectrum of behavioral disorders is associated with Sotos syndrome, some of the most common behavioral problems that have been reported in the literature include aggression, tantrums, anxiety, and attention-deficit/hyperactivity disorder and ASD symptomatology (Gajre et al, 2015;Lane et al, 2017). A variety of options may prove helpful in aiding these children's social and behavioral skills development.…”
Section: Social-emotional and Behavioralmentioning
confidence: 99%
“…Aggressive behaviour and/or tantrums were reported in six studies (Compton et al, 2004;Gajre, Mhatre, & Vijaykumar, 2015;Gomes-Silva, Ruviére, Segatto, De Queiroz, & De Freitas, 2006;Mauceri et al, 2000;Rutter & Cole, 1991;Trad, Schlefer, Hertzig, & Kernberg, 1991) and were assessed through parental report or psychiatric assessment (see Table 1.3). Of these studies, five employed a case study design and only one of the case studies used a female participant (Trad et al, 1991), despite the syndrome affecting males and females equally.…”
Section: Aggression and Tantrumsmentioning
confidence: 99%
“…In addition, only four participants scored in the clinical range for ADHD. Within the case studies that measured behavioural features of individuals with Sotos syndrome, a total of five participants were reported to have a clinical diagnosis of ADHD (Gajre et al, 2015;Gosalakkal, 2004;Mauceri et al, 2000;Mouridsen & Hansen, 2002). In addition, two cases were reported of individuals who were inattentive, hyperactive and demonstrated a lack of inhibition (Mouridsen & Hansen, 2002;Trad et al, 1991).…”
Section: Attention Deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%